Conversion of plastic waste ( Polyethylene) into useful chemicals - Ahmad Farhan Masrur (2023)
An efficient, microwave assisted process has been developed to recycle low density polyethylene (LDPE) waste into value-added chemicals. Nitric acid was used as an oxidizing agent to achieve rapid and effective oxidative degradation for the production of dicarboxylic acids. Various conditions were evaluated where recycling time and the concentration of oxidizing agent were differed and the end products were defined by FTIR. As a conclusion, the developed method can, thus, contribute to a circular economy and offers new possibilities to increase the value of plastic waste. After only 2 h of microwave irradiation in a concentrated nitric acid solution (0.5 g/mL), the LDPE plastic was transformed to well-defined water-soluble products. The length of the dicarboxylic acids could be modified to some degree by changing the reaction time and concentration of oxidizing agent. Hence, the technique has proved to be quite efficient operating under very mild conditions compared to conventional methods.